A THERANOSTIC NANOPLATFORM FOR SIMULTANEOUS MRI-GUIDED IMAGING AND PHOTODYNAMIC THERAPY OF GLIOBLASTOMA - Sandra Castro; Antonio Rodríguez; Luisa González (Yayasan Adra Karima Hubbi, 2026)
Glioblastoma is the most aggressive primary brain tumor, characterized by infiltrative growth, poor prognosis, and limited response to conventional therapies. The lack of precise treatment guidance and effective localized therapy remains a major obstacle in clinical management. This study aims to develop a theranostic nanoplatform capable of simultaneous magnetic resonance imaging (MRI)–guided visualization and photodynamic therapy (PDT) to improve treatment precision and therapeutic efficacy in glioblastoma. An experimental nanomedicine approach was employed, involving the synthesis and physicochemical characterization of a multifunctional nanoparticle integrating MRI contrast agents and photosensitizers. Imaging performance, photodynamic activity, cellular uptake, and therapeutic efficacy were evaluated through in vitro assays and in vivo glioblastoma models. The results demonstrate that the theranostic nanoplatform provides strong MRI contrast enhancement, enabling accurate tumor delineation, while simultaneously generating high levels of reactive oxygen species upon light activation. MRI-guided photodynamic therapy resulted in significant tumor cell apoptosis, reduced tumor volume, and minimal damage to surrounding healthy brain tissue compared to non-guided treatments. In conclusion, the developed theranostic nanoplatform successfully integrates diagnostic imaging and therapy into a single system, enabling precise, image-guided photodynamic treatment of glioblastoma. This strategy represents a promising advancement in precision neuro-oncology and offers a foundation for future clinical translation of integrated nanotheranostic approaches.